Cord Blood T Cells Retain Early Differentiation Phenotype Suitable for Immunotherapy After TCR Gene Transfer to Confer EBV Specificity. Issue 1 (27th September 2012) - Frumento, G.; Zheng, Y.; Aubert, G.; Raeiszadeh, M.; Lansdorp, P. M.; Moss, P.; Lee, S. P.; Chen, F. E.
<x xml:space="preserve">Abstract</x> Adoptive T cell therapy can be effective for Epstein–Barr virus (EBV)‐associated posttransplant lymphoproliferative disease and melanoma. Transducing high‐affinity TCR genes into T lymphocytes is an emerging method to improve potency and specificity of tumor‐specific T cells. However, both methods necessitate in vitro lymphocyte proliferation, generating highly differentiated effector cells that display reduced survival and antitumor efficacy postinfusion. TCR‐transduction of naive lymphocytes isolated from peripheral blood is reported to provide superior in vivo survival and function. We utilized cord blood (CB) lymphocytes, which comprise mainly naive cells, for transducing EBV‐specific TCR. Comparable TCR expression was achieved in adult and CB cells, but the latter expressed an earlier differentiation profile. Further antigen‐driven stimulation skewed adult lymphocytes to a late differentiation phenotype associated with immune exhaustion. In contrast, CB T cells retained a less differentiated phenotype after antigen stimulation, remaining CD57‐negative but were still capable of antigen‐specific polyfunctional cytokine expression and cytotoxicity in response to EBV antigen. CB T cells also retained longer telomeres and in general possessed higher telomerase activity indicative of greater proliferative potential. CB lymphocytes therefore have qualities indicating prolonged survival and effector function favorable to immunotherapy, especially in settings where donor lymphocytes are unavailable such as in solid organ and CB transplantation.